AB0963 Shoulder Involvement in Daily Practice – an Ultrasound Study. (10th June 2014) - Vreju, F.; Chisalau, B.; Gofita Cojocaru, I.; Ivan, M.; Rosu, A.; Ciurea, P.
Abstract : Objectives: To investigate what is the type of shoulder involvement in daily practice and in what kind of diseases it occurs Methods: We enrolled 40 consecutive patients with shoulder US findings, with a mean age 59, 42±7, 5 years and different comorbidities. All patients underwent clinical, biologic and ultrasonographic assessment and they all signed the informed consent. The mean ESR was 26, 6±24, 6 and the cholesterol level was 212, 74±49, 6. Results: The most frequent US finding was subacromial-subdeltoid (SASD) boursitis, which we found in 19 out of 40 patients (47, 5%), followed by the supraspinatus tendon involvement, in 15 out of 40 patients (33, 3%) and long head of biceps brahialis tendinitis in 11 patients (27, 5%). Patients with bilateral SASD bursitis had rheumatoid arthritis (RA) as a main diagnosis. Between the 21 patients with any SASD boursitis, the most frequent diagnosis was RA (11 patients, 52, 4%), followed by traumatic involvement of the shoulder (6 patients, 28, 6%). In the same way, supraspinatus tendon lesion was mainly found in RA patients (8, 57, 14%), followed by traumatic involvement of the shoulder (4, 28, 6%). Calcifications were found mainly in traumatic involvement of the shoulder, followed by gout and RA patients. Conclusions: Most patients with shoulder involvement were rheumatoid arthtritis patients and those with traumatic lesions. Patients with boursitis or fluid in the BB tendon sheet were mainly rheumatoid arthritis patients and in the same time, patients with calcifications were mainly those with traumatic shoulder history. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6067